Case Report: developmental delay and intellectual disability linked to a maternally inherited derivative chromosome 3 from a t(3;8) translocation - León, Andrés; Aguirre, Alex S.; Lindstrand, Anna; Ek, Marlene; Romero, Vanessa I. (Frontiers in Genetics, 2025)
Chromosomes 3 and 8 harbor genes essential for neurodevelopment, skeletal formation, and metabolic regulation. We report a case of two half-siblings with neurodevelopmental delay and intellectual disability who inherited a derivative chromosome 3 from their asymptomatic mother. Chromosomal microarray analysis first identified a 7.12 Mb deletion in 3p26.3–p26.1 and a 48.86 Mb duplication in 8q22.1–q24.3, and findings were further characterized by whole genome sequencing and manual structural interpretation. The 3p deletion involved four pathogenic genes (CHL1, CNTN6, CNTN4, ITPR1) associated with cognitive impairment, ataxia, and motor dysfunction. The 8q duplication affected 50 dosage-sensitive genes implicated in developmental and neurological disorders. Together, these chromosomal imbalances explain the siblings’ phenotype and underscore the contribution of gene dosage effects to neurodevelopmental disease. This case highlights the utility of combining chromosomal microarray and genome sequencing in the diagnosis of complex rearrangements and emphasizes the importance of early genetic counseling and intervention.